VARK learning styles and online education: Case Study - Idrizi, Ermira; Filiposka, Sonja; Trajkovikj, Vladimir (My University, 2018)
In this paper we seek to understand the outcomes of online education by observing the role of learning styles. Under the assumption that the behaviors that maximize learning are dependent on the delivery method, we compared learning outcomes of students participating in two classes set up on an interactive e-learning platform. Our results show that learning styles are variables worthy of consideration in online settings, even though the correlation among learning styles and test results does not indicate a significant association. Specifically, we argue that online education demands a particular set of behavioral patterns (i.e., low companionship, achievement orientation) necessary to navigate the eccentricity of online education (e.g., social isolation, schedule flexibility). We discuss the theoretical implications of our results in the context of online education and offer practical suggestions for online teaching design.
Keywords: Quality of Experience; VARK; Online Education